Getting Off to a Shaky Start: Specificity in Planning and Feedforward Control During Sensorimotor Learning in Autism Spectrum Disorder. Issue 3 (29th October 2019) - Foster, Nathan C.; Bennett, Simon J.; Causer, Joe; Elliott, Digby; Bird, Geoffrey; Hayes, Spencer J.
Abstract : Whilst autistic individuals develop new internal action models during sensorimotor learning, the acquired movements are executed less accurately and with greater variability. Such movement profiles are related to differences in sensorimotor integration and/or altered feedforward/feedback sensorimotor control. We investigated the processes underlying sensorimotor learning in autism by quantifying accuracy and variability, relative timing, and feedforward and feedback control. Although autistic individuals demonstrated significant sensorimotor learning across trials, which was facilitated by processing knowledge‐of‐results feedback, motor execution was less accurate than non‐autistic individuals. Kinematic analysis indicated that autistic individuals showed significantly greater spatial variability at peak acceleration, but comparable spatial variability at peak velocity. These kinematic markers suggest that autistic movement profiles are driven by specific differences in sensorimotor control processes (i.e., internal action models) associated with planning and regulating the forces required to execute the movement. The reduction of variability at peak velocity indicates intact early feedback‐based sensorimotor control in autism. Understanding how feedforward and feedback‐based control processes operate provides an opportunity to explore how these control processes influence the acquisition of socio‐motor actions in autism. Autism Res 2020, 13: 423–435 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Autistic adults successfully learned a new movement skill by physically practising it, and using feedback about how well they had done to become more accurate. When looking at the movements in detail, autistic adults were more variable than non‐autistic adults when planning (e.g., how much force to use), and performing, the movement. These differences impact how autistic individuals learn different types of movement skills, which might influence how other behaviours (e.g., imitation) are acquired that support social interaction.